« À la gloire des Américains », le monument commémoratif du Verdon-sur-Mer - Claire Steimer (In Situ)
Since the sixteenth century, the estuary of the Gironde has been dominated by the famous Cordouan lighthouse, but for a few years during the twentieth century, this monument was eclipsed by a gigantic concrete construction towering over the nearby Grave point at Verdon. It was a commemorative monument designed to pay homage to the American allies which came to France’s help in 1917 just as La Fayette had left France, in 1777, to help the insurgent American colonies. A subscription launched in 1919 in order to finance the project was the beginning of a long process which saw the beginning of the monument’s construction only in 1926. The monument was completed in 1938. It was a collective work designed primarily by the sculptor Albert Bartholomé with help from the architect André Ventre and the sculptors Henri Navarre and Antoine Bourdelle. On 30 July 1942, only four years after the inauguration of the monument, it was dynamited by the German forces of occupation.